Metabolic reset purification program improves antioxidant balance and gut microbiome in individuals transitioning to a healthier diet - Panda, Chinmayee; Kruse, Ralph; Williams, Kaya; Nance, Brea; Gudavalli, Maruti; Pourafshar, Shirin; Metzger, Brandon; Komarnytsky, Slavko (Frontiers in Nutrition, 2025)
A healthy diet helps transition individuals towards numerous long-term metabolic benefits but is challenging to maintain. Supplementation with additional whole food-based concentrates and herbs may support this shift by enhancing metabolic resilience. This randomized, controlled, crossover study evaluated a 21-day purification program emphasizing plant foods and whole food supplementation on metabolic detoxification, oxidative stress, and gut microbiota composition. Participants followed a plant-based diet for 7 days, with lean proteins introduced from days 8–21. Whole food supplements rich in polyphenols, glucosinolates, and prebiotic fibers were included to support metabolic and gastrointestinal function. The intervention group exhibited 9% (p < 0.0001) reduction in ROS-associated oxidative stress compared to diet alone, suggesting enhanced redox balance. Additionally, the intervention group exhibited higher urinary creatinine levels, indicating enhanced kidney filtration efficiency (p = 0.03). Self-reported stress levels decreased by 36% (p = 0.049) in the intervention group, with a notable reduction in anxiety related to future uncertainty, demonstrating the psychological benefits of dietary supplementation. Gut microbiome analysis revealed a reduction in Proteobacteria, a phylum associated with chronic metabolic and inflammatory diseases, and beneficial increases in Ruminococcus gnavus, Lactobacillus zeae, and Roseburia faecis, which contribute to gut barrier integrity and butyrate production. These findings highlight the potential of whole food-based supplementation to enhance dietary transitions by reducing oxidative stress, supporting kidney function, alleviating psychological stress, and modulating gut microbiota composition.Clinical trial registrationNCT05877365.